Biotechnology Application in Wood Industry: Utilization of Phenol Oxidase Enzyme as a Renewable Binder in MDF Manufacture - Alireza Kharazipoor (Regional Information Center for Science and Technology (RICeST), 2012)
Enzymatic activation of lignin on pinewood TMP (Thermo-Mechanical Pulp) fibers for MDF production was investigated using electronic microscopic technique. Two systems: laccase mediator and laccase without mediator were used. MDF was made with laccase as biological catalysts in both wet and dry process. Incubation of fibers with commercially available Trametes versicolor laccase was performed in aqueous solution (wet process) or the enzyme was sprayed onto the fiber (dry process).  Both laccase mediator and laccase without mediator imparted major impact on the optimization of physico-mechanical properties to achieve minimum requirement of standard. Boards produced with fiber-treated with laccase were found to have higher mechanical strength than non-treated binder-free control boards. Best board properties (bending strength, internal bond strength and  swelling) were observed after an incubation of 10-15 min at pH 5.6 and a concentration of 100 U/ml laccase with a mediator (4- Hydroxy benzoic acid 98%) concentration of 10 mM added at 3 min intervals . Electron-microscopic micrographs of enzyme-bonded fibers showed that the application of mediator enhances laccase reaction and, most importantly, the substrate spectrum of the enzymes broadens dramatically. Laccase (phenol oxidase enzymes) serves as an activator of lignin by radical production. Certainly it can be deduced from these studies, that enzymatic treatment altered the surface properties of the fibers. Laccase mediator treated fibers showed a marked increase in the hydrophobicity.